A relação de amizade nas redes sociais de estudantes universitários de Natal/RN - Siqueira, Phellipe Vasconcelos Cavalcanti (2011)
The basis of sociability in humans is based on cooperation. The relationship of friendship is vital to the social, emotional and cognitive development of an individual and can be understood as a consequence of selection for reciprocal altruism in humans. The period of adulthood is considered very suitable and appropriate for the investigation of the relations of friendship, but the Brazilian literature on friendship in adults is still nascent. Therefore, the objective was to characterize the relationship of friendship among college students. The study gathered 500 students from higher education institutions in the city of Natal-RN, Brazil, and 250 women (average age 24.1 ± 7.66 years) and 250 men (mean age 26.77 ± 9.64 years). Two questionnaires anonymously and individual were applied: a sociodemographic questionnaire and the other with the desired characteristics in idealized friends. Study 1 assessed the degree of importance of characteristics in the process of choosing a friend of the same sex and opposite sex of the participant. Study 2 investigated the relationship between patterns of idealization of friends and self-assessment of participants. Overall, were the preferred characteristics "Companionship" and "Sincerity" to idealized friends. We also found the influence of sex on the characteristics attributed to an female ideal friend, with emphasis on men for "Beauty/Good looks" and "Intelligence" and women to "Companionship" and "Sincerity". Finally, we observed a positive correlation between participants' self-assessment and preferences for the characteristics of the friends devised. This study revealed important elements for understanding the relationship of friendship, specifically the process of choosing friends. The results reinforce the importance of studying the relationship of friendship to a better understanding of human social behavior.